Attitude of Medical Students towards Biochemistry and Its Integration through Problem-Based Learning - Pandey, Rachana; Risal, Prabodh (Nepal Journal of Health Sciences, 2022)
Introduction: Biochemistry is an important but volatile subject for undergraduate medical students and is included in integrated organ-based system with problem-based learning method in the curriculum of Kathmandu University School of Medical Sciences. Objective: This study was conducted to assess students’ attitudes toward Biochemistry and its integration into problem-based learning. Methods: It was a descriptive cross-sectional study that lasted 5 months (October 2020-February 2021) after ethical approval from the Institutional Review Committee- KUSMS. Among 150 students participated in the study, 51 were girls and 99 were boys. After taking consent, a pretested self-assessment semi structured questionnaire with a five point Likert scale for each question was used. Out of the statements in the questionnaire, eight questions were positive statements. Mean for each statement was calculated along with average mean score for each positive and negative statements. Results: The mean positive score was 3.06 for the attitude towards studying Biochemistry. The mean score towards the negative statements was 2.4. The mean score was 3.36 for positive statements towards attitude of students towards integration of Biochemistry in problem-based learning whereas the mean score of negative statements was 3.41. Conclusions: Students had overall positive attitude towards studying Biochemistry and its integration into an organ system based curriculum using problem-based learning.